Mycobacterium avium subsp. paratuberculosis detected in the reproductive tract of cows from an infected herd - Pribylova, R; Slana, I; Cech, S; Kralova, A; Pavlik, I (Reproduction in domestic animals, 2013)
Mycobacterium avium subspecies paratuberculosis (MAP), the causal agent of paratuberculosis, was detected by quantitative real-time IS900 PCR in the follicular fluid from the reproductive tracts of cows originating from one infected herd. As well as being detected in follicular fluid of cows shedding bacteria in their faeces, MAP was also detected in the follicular fluid of one apparently healthy, non-shedding individual cow. The finding of MAP in follicular fluid is unexpected and could contribute to the lower viability of embryos and resultant lower pregnancy rate. In addition to finding contaminated follicular fluid, vaginal and uterine flush fluids were determined to be positive for the presence of MAP in 75% and 56.3% of the time of the cattle currently shedding MAP in their faeces, respectively. The presence of MAP in different parts of the reproductive tract was seen in clinically as well as subclinically infected cows. These findings extend our currently scant and contradictory knowledge about the dissemination of MAP in the reproductive tract of female cattle.
Keywords: Pregnancy Complications, Infectious; Feces; Female; Animals; infekční komplikace v těhotenství; feces; ženské pohlaví; paratuberkulóza; Mycobacterium avium subsp. paratuberculosis; Cattle; ženské pohlavní orgány; Genitalia, Female; Paratuberculosis; zvířata; těhotenství; skot; Pregnancy